Effect of Temperature on the Thermal Conductivity of Rocks and Its Implication for In Situ Correction. (4th May 2021) - Chen, Chi; Zhu, Chuanqing; Zhang, Baoshou; Tang, Boning; Li, Kunyu; Li, Wenzheng; Fu, Xiaodong
Abstract : Detailed knowledge of the effects of temperature on the thermal conductivity (λ ) of rocks is essential for investigating the geothermal regime of basins and their thermal evolution. In this study, the λ of four rock types (carbonate, clastic, intrusive, and volcanic rocks) were measured at temperatures of 25°C, 50°C, 100°C, 150°C, 200°C, 250°C, and 300°C using the Transient Plane Source (TPS) approach, which is accurate to ±3%. Experimental results demonstrate that the λ of carbonate and clastic specimens decrease strongly with increasing temperature. In contrast, the λ of intrusive and volcanic rocks are relatively insensitive to temperature. The temperature (T ) dependence of λ can be classified into three groups in terms of the value of λ at 25°C. The first group is composed of rocks characterized by high λ (>4.5 W/m·K) at room temperature, for which the curves of λ − T exhibit a concave pattern. The second group consists of rocks with a moderate λ (2.5~3.5 W/m·K), in which the curves tend to be a straight line. The last group comprises rocks with a low λ (<2.5 W/m·K), exhibiting convex curves. There exists a close relationship between the λ at 25°C and its rate of decrease (α ). The absolute value of α increases with the λ at 25°C rising. The relationship between the two values can be fitted by the equation y = a x + b 1 / x + c to derive the fitting parameters a, b, and c ; by this equation with known fitting parameters, the λ of the deep carbonate rocks of the Tarim Basin have been estimated.